Risk and protective factors for bullying victimization among AIDS-affected and vulnerable children in South Africa. - Cluver, L; Bowes, L; Gardner, F (Elsevier, 2010)
OBJECTIVES: To examine whether bullying is a risk factor for psychological distress among children in poor, urban South Africa. To determine risk and protective factors for bullying victimization. METHOD: One thousand and fifty children were interviewed in deprived neighborhoods, including orphans, AIDS-affected children, streetchildren, and child-headed households. Using standardized scales, children reported on bullying victimization, psychological problems, and potential risk and protective factors at individual, peer, family, and community levels. RESULTS: 34% of children reported bullying victimization. Bullied children showed higher levels of anxiety, depression, suicidal ideation, and post-traumatic stress, as well as higher levels of clinical-level disorder. Risk factors for being bullied were being a victim of physical or sexual abuse or domestic violence at home, living in a high-violence community, and experiencing AIDS-related stigma (independent of sociodemographic cofactors and child psychological disorder). Protective factors were sibling support and support from friends, although findings suggest that friendship groups may also be sources of bullying for AIDS-affected children. CONCLUSIONS: Bullying is an independent and important risk factor in child psychological distress in South Africa. Children victimized at home or in the community are more likely to be bullied, suggesting a cycle of violence. PRACTICE IMPLICATIONS: Those working with children in Southern Africa should be alert to risk of bullying, especially among abused or AIDS-affected children. Interventions combating community violence and AIDS-related stigma may have additional positive impacts on bullying, and promotion of peer and sibling support may reduce bullying victimization among high-risk children.